A Study to Assess the Effectiveness of Information, Education and communication on Knowledge and Practice regarding MR Vaccination among the Mothers in Selected Slum Areas of Pune City - Shaikh Salim Karim1, Jasneet Kaur2 , Mangesh Jabade3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Measles is a very contagious disease which continues to become the killer disease for most of the childrenand infants. On the other side Rubella Infection also is deadly dangerous especially in the vulnerablepopulation of pregnant women where it disables a child for life with congenital rubella syndrome1. Thismay leads blindness, deafness, and other congenital cardiac defects. Bothe the diseases, however, can beprevented with a safe and effective vaccination of the long term immunity2. This immunization directlycontributes to the reduction of under-five child deaths across the country population, thereby reducing thedisabilities. The present study title: “A Study to Assess the Effectiveness of Information, Education andcommunication on Knowledge and Practice regarding MR Vaccination among the Mothers in Selected SlumAreas of Pune City.” The main purpose of the study was to assess the knowledge, practice and to evaluatethe effectiveness of IEC regarding MR vaccination among mothers of selected slum areas of Pune city andto determine associations of the findings with socio demographic variable. Material and Methods: A Preexperimental, one group-Pre- test post-test design was adopted for study . Study carried out on 80 samplesas below 15yrs. children in selected slum area. The non-probability convenience sampling technique wasused to collect the data through structured questionnaire and observational checklist. Ethical clearancewas Obtained from Institutional ethics committee. Data analysis was done mainly using descriptive andinfrantial statistics. Result: The mean post test score 14.27( SD=1.64) was higher than the mean pretestscore 8.48(SD=2.9) .The computed t-test statistic value is 15.124733, Corresponding p-value was 0.000,which is small (less than 0.05)and for the practice mean post test score 38.5(SD=7.63)was higher thanthe mean pretest 26.36(SD=4.25). As the calculated t-value is 12.725452 and p- value was 0.00, whichsmall(less than 0.05.Conclusion:Study conclude that the knowledge and practice of mothers was inadequatein pre-test but then after the administration of IEC there was an increase in the knowledge and practicesabout MR vaccination, so IEC was effective in increasing the knowledge and practice of mothers regardingMR vaccination.Recommendation: A similar study can be conducted in pediatric hospital settings, in PHSand CHC center in rural areas, and carried out to evaluate the efficiency of various teaching strategies likeself-instruction module, pamphlets, leaflets, on measles and Immunization.